Childhood Neglect, Rejection Sensitivity and Relational Patterns among Indian Adults - Alisha Sara Shibu; Soumya Simon (International Journal of Indian Psychȯlogy, 2022)
Understanding the relationship and the impact of Childhood Neglect (CN) on Rejection Sensitivity and thus formed and already established Relational Patterns can help us modify the same in a better way and deal with it in a healthier manner. The study examined the relationship of Rejection Sensitivity across subtypes of Childhood Neglect and Relational Patterns. The study was conducted on (n = 220) adults falling between the age group of 18-40 years.  Data was collected through google forms using the tools The Multidimensional Neglectful Behaviour Scale, Rejection Sensitivity Questionnaire, Adult version, Relationship Scales Questionnaire. Correlation analysis between the study variables showed significant positive and negative relationship between variables. t-test showed that there is significant differences in males and females with respect to emotional neglect and that males faced more emotional neglect.  Regression analysis helped understand the percentage impact of Childhood Neglect and Fearful Relational Pattern on Rejection Sensitivity. The research robustly establishes a correlation between childhood neglect, particularly emotional neglect, and rejection sensitivity in Indian adults. This insight sheds light on the lasting imprint of CN on individuals’ interpersonal relationships. The study also underscores the importance of addressing emotional needs during childhood to foster healthier and secure attachment styles in adulthood.